2006
DOI: 10.1016/j.virol.2005.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of RNA polymerase II on the SV40 genome occurs coordinately with the early to late transcriptional switch

Abstract: The pattern of organization of RNA polymerase II (RNAPII) in wild-type and mutant cs1085 SV40 chromosomes isolated between 30 min and 48 h post-infection was determined using a combination of chromatin immunoprecipitation (ChIP) techniques. During the course of a wild-type infection, we observed a slow but significant decline in the relative occupancy of RNAPII at the early region and a corresponding increase in occupation in the late region. In the promoter, occupancy began high, decreased to a minimum at 8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(80 citation statements)
references
References 34 publications
7
73
0
Order By: Relevance
“…We expected that the immune selected SV40 chromatin would consist of chromosomes with RNAPII located in the promoter which were undergoing initiation, chromosomes with RNAPII located in coding regions which were undergoing transcriptional elongation, and chromosomes with RNAPII located in either the promoter or coding regions in which the RNAPII was paused. We confirmed that antibody to RNAPII could be used to immune select transcribing SV40 chromosomes using a modified ChIP procedure that we refer to as immune selection and fragmentation (ISF) (6,7) . In the ISF procedure the immune selected transcribing SV40 chromosomes were fragmented by sonication into bound chromatin fragments that contained RNAPII and soluble chromatin fragments that lacked RNAPII.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…We expected that the immune selected SV40 chromatin would consist of chromosomes with RNAPII located in the promoter which were undergoing initiation, chromosomes with RNAPII located in coding regions which were undergoing transcriptional elongation, and chromosomes with RNAPII located in either the promoter or coding regions in which the RNAPII was paused. We confirmed that antibody to RNAPII could be used to immune select transcribing SV40 chromosomes using a modified ChIP procedure that we refer to as immune selection and fragmentation (ISF) (6,7) . In the ISF procedure the immune selected transcribing SV40 chromosomes were fragmented by sonication into bound chromatin fragments that contained RNAPII and soluble chromatin fragments that lacked RNAPII.…”
Section: Introductionmentioning
confidence: 53%
“…At 8 hours post-infection in SV40 chromosomes from wild-type virus, we observed that RNAPII occupancy of the promoter and early region was relatively low consistent with down-regulation, while in a mutant of SV40 (cs1085) in which the T-antigen binding site was lacking and down-regulation could not occur the occupancy of the promoter and early region was very high. Since the occupancy of the SV40 genome during the course of infection correlated directly with the known pattern of transcription, we concluded that we were immune selecting transcribing SV40 chromosomes using antibody to RNAPII (7) .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations